1990
DOI: 10.1530/acta.0.1230317
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies reveal circulating growth hormone of high molecular weight not detectable by conventional assays

Abstract: A radioimmunoassay based on a monoclonal antibody, Mc-ab 1, which was raised against growth hormone but cross-reacted with human placental lactogen yielded higher GH immunoreactivity levels in serum than one based on a polyclonal antiserum. This discrepancy was noted in subjects with normal GH secretion as well as in patients with GH insufficiency. To characterize this GH immunoreactivity detected by Mc-ab 1, affinity purification and molecular sieve chromatography of serum were performed. High molecular weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…This is in accordance with our previous findings in patients with GH insufficiency. Despite nondetectable GH levels in these patients, GH was found in high molecular weight complexes after molecular sieve chromatography of their sera [8], It has recently been suggested that the decreasing level of serum GH throughout pregnancy is due to a suppression of pituitary GH [17]. Our results give rise to another explanation for the low levels of pitu itary GH in serum at the end of gestation, namely the presence of GH complexes of large molecular mass, which are detectable in unfractionated serum only by a few antibodies raised against GH such as our here reported Mab 1.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This is in accordance with our previous findings in patients with GH insufficiency. Despite nondetectable GH levels in these patients, GH was found in high molecular weight complexes after molecular sieve chromatography of their sera [8], It has recently been suggested that the decreasing level of serum GH throughout pregnancy is due to a suppression of pituitary GH [17]. Our results give rise to another explanation for the low levels of pitu itary GH in serum at the end of gestation, namely the presence of GH complexes of large molecular mass, which are detectable in unfractionated serum only by a few antibodies raised against GH such as our here reported Mab 1.…”
Section: Discussionmentioning
confidence: 78%
“…An initial character ization of a high molecular weight GH was described [8], The aim of this work was to further characterize the GH immunoreactivity detected by Mab 1 by studying the immunoreactivity in serum during pregnancy concomi tantly with determinations of GH, PL, prolactin (PRL), insulin-like growth factor I (IGF-I) and IGF binding pro tein-1 (IGFBP-1). Furthermore, pooled serum from late pregnancy was fractionated according to molecular size and analyzed with regard to GH and PL immunoreactiv ity.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma GH was determined in a RIA based on a monoclonal antibody (Mab) against GH, Mab 3, previously described [24], The detection limit for the assay was <1.6 pg/1. Mab 3 does not crossreact with PL, PRL and the gene variant of GH and is accordingly specific for pituitary GH (GH-N) [4], Plasma levels of PL and PRL were measured by RIA kits from Pharmacia Diagnostics AB (Upp sala, Sweden) and Farmos Diagnostica (Turku, Finland), respective ly.…”
Section: Methodsmentioning
confidence: 99%
“…Scrum levels of GH and PL were determined by RIA kits from Wellcome Foundation Ltd. (Dartford, UK) and Pharmacia AB (Uppsala, Sweden), respectively. PL was also measured by an RIA with a monoclonal antibody, Mab 1, against GH which cross-reacts with PL [8], This assay also recognizes high molecular weight GH [9], Human CG, OE, and P4 in serum were analyzed by RIA kits from Diagnostic Products Corporation (Los Angeles, Calif., USA) and serum SHBG with an RIA kit from Farmos Diagnostica. …”
Section: Methodsmentioning
confidence: 99%